Sir Oswald Mosley's contribution to the Interwar Policy Debate and Fascist Economics - Emilio Ocampo (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2020)
After being dormant for decades, in the last two decades, right-wing populism resurfaced strongly in Europe and the US channeling a reaction against globalization. This resurgence has prompted economists to pay increasing attention to populist economics. Current versions of right wing populism share many elements with early fascism, particularly the type that developed by the British Union of Fascists (BUF) in the UK under the leadership of Sir Oswald Mosley. Less aggressive and racist than its continental counterparts, one of its pillars was isolationism, which figures prominently in the platforms of modern populist parties in Europe and North America. Although more sophisticated in his economic thinking than Hitler and Mussolini, Mosley's was less successful politically. His stubborn obnoxiousness and inability to acknowledge his mistakes cemented his status as a political pariah and contributed to the academic neglect of his 1930 program of radical economic reform which he later incorporated into the BUF's platform. The study of Mosleynomics also has historical value. Mosley's proposals not only contributed to the interwar policy debate but also anticipated many key elements of the economic policies of fascist and non-fascist regimes on both sides of the Atlantic, not only in the US, Germany and Italy in the 1930s but also in the UK under the Labor Party and Argentina under Perón in the immediate postwar. This essay seeks to contribute to fill a gap in the literature, by tracing the intellectual roots and evolution of Mosley's economic policy proposals.
Keywords: B00; B29; E60; E65; N14; N16; O23; P40; P47; 330; Peronism; Fascism; Economic Policy; Argentina